Positron lifetimes of bare and hydrogenated zirconium vacancies in cubic yttria-stabilized zirconia: an ab initio study. (23rd May 2019) - Marinopoulos, A G
Abstract: Recent studies by positron-annihilation spectroscopy (PAS) in single-crystal and nanostructured yttria-stabilized zirconia (YSZ) revealed extensive positron trapping at vacancy-type point defects and other structural imperfections. The present work reports first principles calculations of formation energies and positron lifetimes of Zr vacancies in 10.3 mol% cubic YSZ. The lifetime calculations are based on two-component density-functional theory within the local-density approximation for the electron-positron correlation energy. Gradient-correction effects were also examined. Zr monovacancies were found to be potent trapping sites for positrons with large binding energies and lifetimes in excess of 220 ps. A strong dependency of the lifetimes on the Zr site and local coordination number was observed, a consequence of the structural disorder of the stabilized lattice. In contrast, oxygen vacancies did not act as attractive centers for positrons, either as single defects or as nearest neighbors to seven-fold coordinated Zr vacancies. Defect association of the Zr vacancies with hydrogen led to stable ( -H) complexes with hydrogen bound to oxygen ions which are nearest neighbors to the vacancies. The negatively-charged ( -H) defects were also found to trap positrons with corresponding lifetimes strongly dependent upon the hydrogen content within the complex.